West Nile Virus: An Update Focusing on Southern Europe - Lara Carrasco; Maria Jose Utrilla; Beatriz Fuentes-Romero; Aitor Fernandez-Novo; Barbara Martin-Maldonado (Microorganisms)
West Nile Virus (WNV) is a zoonotic, vector-borne pathogen affecting humans and animals, particularly in Europe. The virus is primarily transmitted through mosquitoes that infect birds, which serve as the main reservoirs. Humans and horses are incidental hosts. This review focuses on the epidemiology of WNV in southern Europe, particularly its increasing prevalence. Methods included an extensive literature review and analysis of recent outbreaks. WNV is largely asymptomatic in humans, but a small percentage can develop West Nile neuroinvasive disease (WNND), leading to severe neurological symptoms and fatalities. Horses can also suffer from neurological complications, with high mortality rates. Climate change, migratory birds, and mosquito population dynamics contribute to the virus spread across Europe. Control efforts focus on vector management, and while vaccines are available for horses, none has been approved for humans. Surveillance, particularly of bird and mosquito populations, and further research into the virus molecular structure are crucial for understanding and mitigating future outbreaks.